EL PLANEAMIENTO ESTRATÉGICO DEL TURISMO ECOLÓGICO EN AMÉRICA LATINA: CASO POSADA AMAZONAS DEL PERÚ Y DEL ECUADOR - Sarasara Andrea, Cesar (2012)
In this work we have reviewed existing research at various national and international tourism. The study aims to propose ecological Strategic Planning Ecotourism in Latin America:case Posada Amazonas in Peru and Ecuador to obtain the data, a survey of the native communities of the Amazon of Peru and Ecuador, the analysis of data using the multivariate method, using the factor analysis method has been chosen the higher ranked variables in each group was also used strategic planning techniques. The analysis has established that the native communities are not satisfied with the installation of mining, damaging the ecosystem and support the growth and creation of other eco-tourism enterprises. It is concluded that strategic planning for ecotourism in Latin America is green through strategic partnerships.